2013
DOI: 10.5152/balkanmedj.2013.8042
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Obstructive Pulmonary Disease in Kocaeli: An Industrialised City in Turkey

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is an important cause of mortality worldwide.Aims: The aim of this study was to establish the prevalence of chronic obstructive pulmonary disease (COPD) in residents who were ≥40 years old and living in a heavily industrialised city of Turkey, Kocaeli, using the Burden of Obstructive Lung Disease Initiative questionnaire.Study Design: Cross-sectional study.Methods: 1035 residents ≥40 years old and living in Kocaeli were surveyed. Spirometry and the basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…It was reported that the global prevalence of COPD is 11.7%, and 3 million people die due to COPD every year (GOLD, 2022). Epidemiological studies conducted in the provinces of Kocaeli, Zonguldak, and Kayseri in Turkey reported the prevalence of COPD as 13.3%, 11.1%, and 17.6% (Arslan et al, 2013;Örnek et al, 2015;Timur et al, 2020). These rates were similar to the reported global prevalence of COPD.…”
Section: Introductionsupporting
confidence: 71%
“…It was reported that the global prevalence of COPD is 11.7%, and 3 million people die due to COPD every year (GOLD, 2022). Epidemiological studies conducted in the provinces of Kocaeli, Zonguldak, and Kayseri in Turkey reported the prevalence of COPD as 13.3%, 11.1%, and 17.6% (Arslan et al, 2013;Örnek et al, 2015;Timur et al, 2020). These rates were similar to the reported global prevalence of COPD.…”
Section: Introductionsupporting
confidence: 71%
“…However, the number of the female patients in our study was very low. In developing countries like Turkey, the higher rate of smoking and COPD among males is an expected situation [11]. In our study, the prevalence of TGD was found as 25% (3/12) in the female patients and 22% (65/297) in the male patients.…”
Section: Pulmonary Medicinesupporting
confidence: 50%
“…In the present study, the COPD prevalence was lower than the results of previous studies (Gunen et al ., 2008; Deveci et al ., 2011; Arslan et al ., 2013; Dikis et al ., 2015). There might be some reasons to explain the low frequency of COPD in the present study.…”
Section: Discussionmentioning
confidence: 99%